ANALISIS KADAR GULA TOTAL, FLAVONOID, DAN UJI AKTIVITAS ANTIOKSIDAN DARI FORMULASI BROTOWALI DENGAN APEL MANALAGI SEBAGAI MINUMAN FUNGSIONAL - Prasetyo, Irene Nuariza; Anwar, Khoirul (Jurnal Gizi dan Pangan Soedirman, 2024)
Currently, the highest number of deaths in Indonesia is caused by non-communicable diseases. One of the non-communicable diseases is diabetes mellitus which is a metabolic disease. Efforts to prevent diabetes mellitus with non-pharmacological therapy can use plants that have the potential to have anti-diabetic effects. This study aims to make brotowali with manalagi apples as a functional drink which has potential as an antidiabetic and to determine total sugar content, flavonoids, and antioxidant activity with 3 ratios of brotowali : manalagi apple (F1 1:2, F2 1:1, and F3 2:1). This study used a completely randomized design (CRD) with 3 formulations and 3 repetitions. The statistical tests used were Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT). The results showed that F1, F2, and F3 averaged total sugar content respectively 27.4%, 22.3% and 20.9%, the average of flavonoids was 41.7 mgQE/g, 48.8 mgQE/g, and 62.8 mgQE/g, and the average antioxidant activity with IC50 values were 145.5 µg/ml, 109.3 µg/ml, and 92.2 µg/ml. The best formulation of brotowali functional drink with manalagi apple is formula F3 with total sugar content of 20.9%, flavonoid content of 62.8 mgQE/g and antioxidant activity with IC50 value of 92.2 µg/ml.